Analytical study of Novel "Udaas Naslain" in the Context of Binaries - Riaz, Hajra; Afzal, Isma (sourcecoder, 2024)
A novel is not only a mirror of life but also an interpreter of an era. Novels are an excellent source of history. Novel "Udaas Naslain" by Abdullah Hussain depicts the era of Indian’s struggle of independence and the period of post-independence. Numerous changes took place in the subcontinent from 1857 to 1947. This period was the third period of European colonialism. In whichever region of the world the settlers established their foothold, they established themselves in those regions based on well-thought-out plans and policies. Abdullah Hussain in his novel "Udaas Naslain" describes the elements of political binary introduced by the settlers. The ideology of neo-colonialism was built on binaries and this narrative was not limited to just gaining power, but to strengthen themselves. Binaries were created on the basis of culture, language, religion, educational system, political system etc. Social classes, feeling of social inferiority is the outcome of colonialism. Novel “Udaas Naslain" has been analyzed on the basis of binary theory in neo-colonialism.